A Retrospective Review of Outcomes and Flap Selection in Free Tissue Transfers for Complex Lower Extremity Reconstruction - Fischer, John P.; Wink, Jason D.; Nelson, Jonas A.; Cleveland, Emily; Grover, Ritwik; Wu, Liza C.; Levin, L. Scott; Kovach, Stephen J. (Journal of Reconstructive Microsurgery, 2013)
Purpose Complex lower extremity wounds present a significant challenge to the reconstructive surgeon. We report a consecutive experience of free tissue transfers for lower extremity reconstruction with a focus on outcomes and flap selection.Methods A retrospective review of all free tissue transfers for lower extremity reconstruction between 2006 and 2011 was performed. Minor complications were defined as nonoperative complications (infection, seroma, hematoma, wound breakdown, and partial loss). Major complication required a surgical intervention (total flap loss, thrombosis, nonunion, amputation, and hematoma).Results A total of 119 free flaps were performed in 114 patients. Reconstructed defects were most commonly derived from acute traumatic (N = 40) or chronic traumatic (N = 34) wounds, oncologic (N = 14), or diabetic (N = 8). Flap loss occurred at a rate of 5.9% and the overall lower extremity salvage rate was 93%. Complications were significantly higher for free tissue transfers to the region of the distal tibia (p = 0.04). Major complications were significantly higher in patients with chronic obstructive pulmonary disease (p = 0.02) and in patients who experienced intraoperative technical difficulties (p = 0.014). Flap loss was significantly higher when the rectus abdominis flap was used (p = 0.02) and when a delayed venous thrombotic event occurred (p = 0.001).Conclusion Patient comorbidities and defect location can be associated with higher rates of complications; flap selection and delayed venous thrombotic events appear to be associated with flap failure.Level of Evidence Prognostic/risk category, level III
Keywords: lower extremity; free flap; outcomes